An Efficient Multi‐Component Synthesis of Highly Functionalized Calix[4]arenes with Pronounced Binding Affinity toward β‐Lactoglobulin. Issue 22 (11th July 2016) - Zadmard, Reza; Akbari‐Moghaddam, Peyman; Darvishi, Shukufe; Mirza‐Aghayan, Maryam
Abstract : A facile and convenient approach for the synthesis of multi‐functionalized calix[4]arenes through multi‐component reactions is described. A series of five new calix[4]arene‐hexaamide derivatives were synthesized, and their structures were elucidated by means of spectroscopic data. The value of this method lies in its operational simplicity, mild reaction conditions, structural diversity of products, and good yields. Furthermore, fluorescence studies demonstrated considerable binding affinity of these new calix[4]arenes toward β‐lactoglobulin protein. Abstract : A new class of highly functionalized calix[4]arenes was synthesized by multi‐component reactions in good yields (70–86 %). Protein‐binding studies carried out with fluorescence spectroscopy revealed that these compounds bind strongly to β‐lactoglobulin.